2014
DOI: 10.1177/0095244314538436
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coupling agents on silicate-based nanofillers/carbon black dual filler systems on the properties of a natural rubber/butadiene rubber compound

Abstract: Nanofillers have been introduced a few years ago, but their application in elastomers is still a challenge. With the existing rubber processing equipment and constraints of rubber mixing, dispersion of nanofillers is difficult. The processability and performance of compounds containing plate- or tube-like silicates in a blend with conventional fillers, such as carbon black (CB), are investigated, and the effect of surface modification of the nanofillers is studied. Processing is facilitated by the replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The role of HNT's surface area and aspect ratio on tensile properties of rubber has previously reported by Pasbakhsh, et al They found that HNT with higher aspect ratio and surface area showed greater tensile strength and elastic modulus than HNT with lower aspect ratio and surface area. Currently, great attempts have been made to investigate the reinforcement of HNT (with/without surface modifiers) in various elastomers including natural rubber (NR), styrene butadiene rubber (SBR), carboxylate styrene butadiene rubber (xSBR), ethylene propylene diene monomer (EPDM), nitrile rubber (NBR), silicone (Q) and fluoroelastomer (FKM) . It is reported that HNT has low compatibility with rubber molecules and, thus, the addition of surface modifiers is required for enhanced rubber‐filler interaction and improved filler dispersion in the nano‐composites …”
Section: Introductionmentioning
confidence: 99%
“…The role of HNT's surface area and aspect ratio on tensile properties of rubber has previously reported by Pasbakhsh, et al They found that HNT with higher aspect ratio and surface area showed greater tensile strength and elastic modulus than HNT with lower aspect ratio and surface area. Currently, great attempts have been made to investigate the reinforcement of HNT (with/without surface modifiers) in various elastomers including natural rubber (NR), styrene butadiene rubber (SBR), carboxylate styrene butadiene rubber (xSBR), ethylene propylene diene monomer (EPDM), nitrile rubber (NBR), silicone (Q) and fluoroelastomer (FKM) . It is reported that HNT has low compatibility with rubber molecules and, thus, the addition of surface modifiers is required for enhanced rubber‐filler interaction and improved filler dispersion in the nano‐composites …”
Section: Introductionmentioning
confidence: 99%
“…TESPD‐modified sample had the lowest torque and increased scorch time. This effect may be explained by less efficient crosslinking reaction and deactivation of curatives due to the presence of some silanol groups on the modified filler, as these groups are known to interact with accelerator . Moreover, unwanted bubble formation may be responsible for the effect.…”
Section: Resultsmentioning
confidence: 99%